Hubungan Kadar Gula Darah Dengan Hipertensi Pada Pasien Diabetes Melitus Tipe 2 Di Wilayah Kerja Puskesmas Teluk Tiram Kota Banjarmasin Tahun 2024 - Unja, Ermeisi Er; Britama, Britama; Trihandini, Bernadetha (LPPM Universitas Sari Mulia, 2024)
Background: Type 2 diabetes is a metabolic disorder characterized by elevated blood glucose levels because the body is unable to utilize insulin effectively. The incidence of type 2 diabetes increases with age and unhealthy lifestyle. Uncontrolled blood glucose levels in patients can lead to various complications, including microangiopathy, which is a problem in large blood vessels (hypertension). Studies state that type 2 diabetic patients with hypertension have a 7 times greater risk of developing terminal renal failure (ESRD) and 2-4 times of cardiovascular disease, such as myocardial infarction, stroke, or death, compared to normotensive type 2 diabetic patients of the same age. Objective: This study aims to identify the association of blood sugar levels with hypertension in patients with type 2 diabetes mellitus. Method: This study uses quantitative cross-sectional method using observation sheet. The sample in the study was 85 respondents selected by purposive sampling technique. Normality test using Kolmogorow-Smirnov test and for bivariate statistical test using Spearman Rank test. Result: The results showed 53 respondents (62.4%) experienced hyperglycemia, with complications of grade 1 hypertension as many as 33 respondents (38.8%). This result shows that the higher the blood sugar level, the more at risk of hypertension. Conclusion: The conclusion of the study showed a significant relationship between blood sugar levels and hypertension in patients with type 2 diabetes with a p-value of 0.000 (<0.05).